Are two different speed endurance training protocols able to affect the concentration of serum cortisol in response to a shuttle run test in soccer players? - Vitalea, J. A.; Povìab, V.; Bellib, E.; Lombardia, G.; Banfia, G.; La Torre, A. (Research in Sports Medicine, 2020)
Soccer involves multiple high-intensity physical, technical and tactical actions; as result of this, soccer training must include high-intensity exercises, which can act as a stimulus to the hypothalamus pituitary-adrenal axis, resulting in a significant increase in circulating cortisol levels. This study examined the effect of 4 weeks of Speed Endurance Maintenance (SEM) and Speed Endurance Production (SEP) on the serum cortisol concentration in response to a 5-meter multiple shuttle run test (5-m MST) in young elite soccer players. Fifteen soccer players were divided to SEM (n = 7) or SEP (n = 8) training group. Blood drawings were performed four times: before and after the 5-m MST at baseline (T1a, T1b) and at follow-up (T2a, T2b). Both training regimes determined a cortisol secretion following the 5-m MST at both baseline and follow-up. Data on delta values highlighted that SEP had greater values than SEM at baseline and registered a significant decrease at the follow-up. This difference is probably due to the lack of specific speed endurance training for players of SEP group prior to the beginning of the protocol. The physiological mechanisms behind the observed biological differences should be deeply investigated.